The winner is innovation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
In northern Nigeria s Jigawa State Mohammed Bah Abba has won the Rolex Enterprise Award for popularising a cooler which keeps food fresh for three days. Made of a clay jar within a jar, with water in the space between, the device is a winner among...